IMPROVEMENT OF SCIENCE LEARNING OUTCOME TO THE THEME HEAT AND ITS TRANSFER THROUGH INQUIRY METHOD FOR FIFTH GRADE STUDENTS OF SDN 1 PEJAGOAN IN ACADEMIC YEAR OF 2019/2020 - Heni Rahmawati; Rokhmaniyah Rokhmaniyah; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract: The research aimed to improve science learning outcomes to the theme heat and its transfer. It was a collaborative classroom action research (CAR) carried out in three cycles. The subjects were students of grade 5A of SDN 1 Pejagoan in academic year of 2019/2020. Data collection techniques were observation, interviews, documentation, and tests. The validity of the data used triangulation of techniques and sources. Quantitative data analysis used descriptive statistics while qualitative data analysis included data reduction, data presentation, and drawing conclusions. The result indicated that the inquiry method improved science learning outcomes to the theme heat and its transfer for students of grade 5A of SDN 1 Pejagoan in academic year of 2019/2020. The average percentages of students learning outcomes were 85.19% in the first cycle, 90.74% second cycle, and 96.30% third cycle. It indicates that the inquiry method improves science learning outcome to the theme heat and its transfer for students of grade 5A of SDN 1 Pejagoan in academic year of 2019/2020.